OP0246 Impact of disease activity measures on sick leave in biologics-treated patients with rheumatoid arthritis: observational data from southern sweden. (15th June 2017) - Wallman, JK; Söderling, JK; Gülfe, A; Kristensen, L-E; Neovius, M; Olofsson, T
Abstract : Background: Sick leave generally represents the earliest phase of work-loss in rheumatoid arthritis (RA) patients, often on the trajectory towards more permanent disability pension. Sick leave may still change with disease activity fluctuations and is thus potentially reversible and accessible for interventions. However, data remain scarce on the importance of modifiable, non-composite disease activity measures for subsequent sick leave in RA patients treated with biologics. Objectives: To study the impact of common, non-composite disease activity measures on sick leave in biologics-treated RA patients. Methods: Study visits of biologics-treated RA patients of working-age (<65y) without disability pension, monitored in the population-based, observational South Swedish Arthritis Treatment Group register 2005–2011, were included (5151 visits; 957 patients). We performed association analyses between various non-composite disease activity measures at each visit and number of objectively assessed sick leave days during the month thereafter, retrieved from the Social Insurance Agency. Separate generalised estimating equation regression models were used, adjusting for age, sex, educational level, disease duration, number of previous biologics, time from start of the present biologic, and calendar year of study visit. Analyses were furthermore stratified on sick leave status the month preceding each visit (no sick leave=0 days out of 30; partial sick leave=1–29 days and full sick leave=30 days) and results are presented as standardised beta coefficients for comparability, with bootstrap-generated 95% confidence intervals. The composite 28-joint disease activity score (DAS28) and the health assessment questionnaire (HAQ) disability score were included as contrast. Results: Out of common, non-composite disease activity measures, visual analogue scale (VAS) global and VAS pain were most strongly associated with sick leave days the month after the study visit, irrespective of baseline sick leave status (Figure). Generally, the more objective measures (erythrocyte sedimentation rate, C-reactive protein and swollen joint count (SJC)) had less impact on subsequent sick leave than the more subjective variables (VAS global, VAS pain, evaluator's global and tender joint count (TJC)). As expected, HAQ showed the strongest association. Conclusions: More subjective disease activity measures have greater impact on sick leave in biologics-treated RA patients than do more objective variables, suggesting a stronger focus on the former ones when targeting work-loss or intervening to reduce it. Disclosure of Interest: J. Wallman Consultant for: Novartis, Celgene and UCB, J. Söderling Grant/research support from: Participated in previous research projects fully or partly funded by Novo Nordisk and Combine Sweden, Consultant for: Served as an external consultant to AbbVie, Merck and Novartis, A. Gülfe: None declared, L.-E. Kristensen Grant/research support from: Oak Foundation, Consultant for: AbbVie, Celgene, BMS, MSD, Novartis, Pfizer, UCB, M. Neovius Grant/research support from: Participated in research projects fully or partly funded by Schering-Plough, AstraZeneca, Novo Nordisk, Pfizer and Roche (unrelated to the current work), Consultant for: Participated in advisory boards for Pfizer (rheumatology) and Abbott (non-rheumatology), T. Olofsson: None declared